Coinhibitory Receptor Expression and Immune Checkpoint Blockade: Maintaining a Balance in CD8+ T Cell Responses to Chronic Viral Infections and Cancer - Okoye, Isobel S.; Houghton, Michael; Tyrrell, Lorne; Barakat, Khaled; Elahi, Shokrollah (Frontiers in Immunology, 2017)
In cancer and chronic viral infections, T cells are exposed to persistent antigen stimulation. This results in expression of multiple inhibitory receptors also called “immune checkpoints” by T cells. Although these inhibitory receptors under normal conditions maintain self-tolerance and prevent immunopathology, their sustained expression deteriorates T cell function: a phenomenon called exhaustion. Recent advances in cancer immunotherapy involve blockade of Cytotoxic T Lymphocyte Antigen-4 (CTLA-4) and Programmed Cell Death 1 (PD-1) in order to reverse T cell exhaustion and reinvigorate immunity, which has translated to dramatic clinical remission in many cases of metastatic melanoma and lung cancer. With the paucity of therapeutic vaccines against chronic infections such as HIV, HPV, HBV and HCV, such adjunct checkpoint blockade strategies are required including the blockade of other inhibitory receptors such as TIGIT, TIM-3, LAG-3 and VISTA. The nature of different chronic viral infections and cancers is likely to influence the level, composition and pattern of inhibitory receptors expressed by responding T cells. This will have implications for checkpoint antibody blockade strategies employed for treating tumors and chronic viral infections. Here we review recent advances that provide a clearer insight into the role of co-inhibitory receptor expression in T cell exhaustion and reveal novel antibody-blockade therapeutic targets for chronic viral infections and cancer. Understanding the mechanism of T cell exhaustion in response to chronic virus infections and cancer as well as the nature of restored T cell responses will contribute to further improvement of immune checkpoint blockade strategies.